Amarillo fish (Girardinichthys multiradiatus) use visual landmarks to orient in space - de Perera, T; Garcia, C (2003)
Fish responsiveness to visual stimuli has been studied extensively in contexts such as female mate choice, predator inspection and schooling, yet surprisingly little work has been conducted on visual orientation in space in fish. Here we report on an experiment designed to test whether Amarillo fish can learn to find a goal within a maze more effectively in the presence of local visual landmarks than otherwise. We found that: (a) Amarillo fish can use landmarks to locate a goal, (b) there was no observed difference in the ability to use visual landmarks between two populations and (c) overall navigational performance differed between two populations of Amarillo fish: individuals from a permanently turbid eutrophic pond performed better than those from a pond with clear waters. We hypothesize that fish that inhabit clear waters possess poorer navigational capabilities than fish from turbid waters because they normally rely on goal-oriented behaviour, which requires neither egocentric nor environmental clues to navigate. This paper adds to the literature on the links between habitat characteristics and population differences in performance.